Non-Invasive Ventilation Strategies in Children With Acute Lower Respiratory Infection: A Systematic Review and Bayesian Network Meta-Analysis - Wang, Zhili; He, Yu; Zhang, Xiaolong; Luo, Zhengxiu (Frontiers in Pediatrics, 2021)
Background: Multiple non-invasive ventilation (NIV) modalities have been identified that may improve the prognosis of pediatric patients with acute lower respiratory infection (ALRI). However, the effect of NIV in children with ALRI remains inconclusive. Hence, this study aimed to evaluate the efficacy of various NIV strategies including continuous positive airway pressure (CPAP), high flow nasal cannula (HFNC), bilevel positive airway pressure (BIPAP), and standard oxygen therapy in children with ALRI and the need for supplemental oxygen. Methods: The Embase, Pubmed, Cochrane Library and Web of Science databases were searched from inception to July 2021. Randomized controlled trials (RCTs) that compared different NIV modalities for children with ALRI and the need for supplemental oxygen were included. Data were independently extracted by two reviewers. Primary outcomes were intubation and treatment failure rates. Secondary outcome was in-hospital mortality. Pairwise and Bayesian network meta-analyses within the random-effects model were used to synthesize data. The certainty of evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation framework. Results: A total of 21 RCTs involving 5,342 children were included. Compared with standard oxygen therapy, CPAP (OR: 0.40, 95% CrI: 0.16-0.90, moderate quality) was associated with a lower risk of intubation. Furthermore, both CPAP (OR: 0.42, 95% CrI: 0.19-0.81, low quality) and HFNC (OR: 0.51, 95% CrI: 0.29-0.81, low quality) reduced treatment failure compared with standard oxygen therapy. There were no significant differences among all interventions for in-hospital mortality. Network meta-regression showed that there were no statistically significant subgroup effects. Conclusion: Among children with ALRI and the the need for supplemental oxygen, CPAP reduced the risk of intubation when compared to standard oxygen therapy. Both CPAP and HFNC were associated with a lower risk of treatment failure than standard oxygen therapy. However, evidence is still lacking to show benefits concerning mortality between different interventions. Further large-scale, multicenter studies are needed to confirm our results.